Unplanned restoration: Pallid swifts recover twenty years after rat removal from a Mediterranean island (Avocetta, 2022)
Results from an experimental study from 1994 suggested that Black Rats, introduced on small Mediterranean islands, restricted Pallid Swift nesting to a small number of sites inaccessible to rats. We report here that the removal of rats in 2000 to restore a seabird population was followed by an unplanned increase of nesting Pallid Swifts through an increase in the number and variety of nest sites used, including low and easily reachable sites.
Keywords: islands; unexpected restauration; nest sites; nest site selection; nest predation